Valorizzare la dignità della persona nelle «norme in materia di consenso informato e di disposizioni anticipate di trattamento» (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
In this paper I will present my study about dignity’s value, highlighting the discrepancy between an objective conception of dignity of life and a subjective consideration related to the dignity of a person. This gap is specifically evident at the “end of life” and it actually represents one of the biggest question for the Italian medical community and in the political landscape. For this reason, I would like to talk about biological will and advanced healthcare directives, which are the latest legal proposals that provide everyone with the right to choose independently on their own body and life.
Keywords: self-determination; rights; dignity; life; living will